Pengaruh Penggunaan Media Sosial Akun Instagram @podcast_somestory dengan Pemenuhan Kebutuhan Informasi kepada para Pengikut - Fachrunisa Zahra; David Rizar Nugroho; Enden Darjatul Ulya; Mulyono Mulyono (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of social media usage on the Instagram account @podcast_somestory toward fulfilling the information needs of its followers. The research employs a quantitative survey method with 100 respondents selected using the Slovin formula. The independent variable (X) consists of social media usage indicators based on the 4C framework (content, communication, connection, collaboration). Meanwhile, the dependent variable (Y) represents information needs fulfillment based on Bimalendu Guha’s Information Need Approaches, which include current, everyday, exhaustive, and catching-up needs. Data analysis techniques include validity and reliability testing, descriptive analysis, correlation testing, and linear regression. The results show that social media usage significantly influences the fulfillment of followers’ information needs. These findings reinforce the Uses and Gratifications theory within the context of social media and provide practical implications for optimizing information delivery strategies on Instagram.